Effect of copper addition on grain refinement of austenite in Fe-8wt.%Ni-(0.3)Wt.% Cu alloy - Junaidi Syarif,; Zainuddin Sajuri, (Universiti Kebangsaan Malaysia, 2010)
The effect of copper addition on martensitic structure and reversion from martensite to austenite behaviours upon heating were investigated to clarify mechanism of grain refinement of austenite in Fe-8wt.%Ni-Cu alloys. Upon water-quenching, the alloys underwent a martensitic transformation that exhibited a typical lath-martensitic structure. It was found that prior-austenite grain and martensite-packet sizes were refined with increasing copper content. The grain refinement was not due to a decrease of grain growth rate of the austenite. However, it was found that nucleation rate of the austenite on reversion was increased by the copper addition. In Fe-8wt.%Ni alloy heated in (austenite+ferrite) region, reversed austenite grains were formed at high angle boundaries such as prior austenite grain boundary and packet boundary. On the other hand, TEM observation of the Fe-8wt.%Ni-3wt.%Cu alloy revealed that fine copper particles precipitated within the martensitic structure and the reversed austenite grains also formed within lath-structures and lath boundary. It means that the copper addition promoted formation of the reversed austenite within martensitic matrix and resulted in the grain refinement of the prior-austenite in Fe-8wt.%Ni-Cu alloy.